PELAKSANAAN PERATURAN DAERAH KABUPATEN JENEPONTO NOMOR 8 TAHUN 2006 TENTANG LARANGAN PEREDARAN MINUMAN BERALKOHOL DAN PENGAWASANNYA DI KECAMATAN BINAMU KABUPATEN JENEPONTO - Andi Kasmawati; Bakhtiar Bakhtiar; Nurhayati Nurhayati (Universitas Negeri Makassar, 2018)
This study aims to determine: (1) Implementation Jeneponto District Regulation No. 8 of 2006, (2) supporting and inhibiting factors Implementation Jeneponto District Regulation No. 8 of 2006. This study is a qualitative descriptive study. The data collection procedures used were interviews and documentation. While data analysis used is qualitative analysis. The results showed that the implementation of the Regional Regulation Kabupatenn Jeneponto No. 8 of 2006 does not operate effectively, this is caused because there are many alcoholic drinks that circulate in the community who can be in stores - stores and houses as well as a lack of public awareness of the existence of these regulations. The supporting factors of Implementation Jeneponto District Regulation No. 8 of 2006 are: (1) Participation of community and religious leaders, (2) cooperation among government officials. While the factors that inhibit the implementation of Jeneponto District Regulation No. 8 of 2006 include: (1) the awareness factor, (2) socialization factors, (3) factors sanctions (4) that habit, (5) follow-up of violations of Bylaw No. 8 in 2006 is still in the stage of non yuspisial namely the lack of investigations and inquiries at the police forces of the civil service